1989
DOI: 10.1159/000480976
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Ranitidine in Critically Ill Infants

Abstract: The pharmacokinetic parameters of ranitidine were studied following administration of a single intravenous dose in 9 critically ill infants. Ranitidine disposition was best described by a biphasic elimination curve. For 8 patients, the mean values for T 1/2, apparent volume of distribution, and total body clearance were 2.09 h, 1.61 l/kg, and 13.93 ml/min/kg, respectively. Based on simulated steady-state concentration profiles, a dose of 0.7 mg/kg administered intravenously every 6 h should maintain serum leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 11 publications
3
15
0
Order By: Relevance
“…12 13 Ranitidine has been considered safe for the treatment of even critically ill neonates 10. The main mode of action of these H 2 blockers is the increase in the gastric pH by decreasing the gastric acid output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 13 Ranitidine has been considered safe for the treatment of even critically ill neonates 10. The main mode of action of these H 2 blockers is the increase in the gastric pH by decreasing the gastric acid output.…”
Section: Discussionmentioning
confidence: 99%
“…The main effect of H 2 blockers is to decrease the gastric acidity and to increase the gastric pH by inhibiting acid production. The serum concentration of ranitidine does not always correlate with gastric pH in neonates10 11 and so this measurement cannot be used to determine the optimal ranitidine dose.…”
mentioning
confidence: 99%
“…1). However, we excluded 13 studies because they were nonrandomized or noncontrolled or focused on pharmacokinetics of drugs (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). One study in Hungarian is pending for evaluation (25).…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The value of t½ el in the study of Fontana et al [20], was more prolonged than that reported by Wiest et al [21] (3.45 vs 2.09 h). Consequently, Cl was less (5.02 vs 13.9 mL/kg/h).…”
Section: Discussionmentioning
confidence: 54%
“…Wiest et al [21], on their part reported t½ el values of 2.09 h; V d, of 1.61 L/kg; and Cl of 13.9 mL/kg/h in neonates from 2 to 21 months of age. A comparison of V d values in both studies with 1.6 L/kg reported in adults by Schaiquevich et al, [22], reveals that plasma protein binding and tissue distributions of this drug are similar in different age groups.…”
Section: Discussionmentioning
confidence: 99%